2016
DOI: 10.1002/2016ms000659
|View full text |Cite
|
Sign up to set email alerts
|

Can nudging be used to quantify model sensitivities in precipitation and cloud forcing?

Abstract: Efficient simulation strategies are crucial for the development and evaluation of high‐resolution climate models. This paper evaluates simulations with constrained meteorology for the quantification of parametric sensitivities in the Community Atmosphere Model version 5 (CAM5). Two parameters are perturbed as illustrating examples: the convection relaxation time scale (TAU), and the threshold relative humidity for the formation of low‐level stratiform clouds (rhminl). Results suggest that the fidelity of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 37 publications
4
31
0
Order By: Relevance
“…7). In line with the findings of Lin et al 57 , the decrease in PRECC to an increase in rhminl is also seen by indirectly affecting the stability of the low-level atmosphere and hence the convection (Fig. 7).…”
Section: Ri Of Parameters On Simulation Of Important Climatic Variablessupporting
confidence: 91%
“…7). In line with the findings of Lin et al 57 , the decrease in PRECC to an increase in rhminl is also seen by indirectly affecting the stability of the low-level atmosphere and hence the convection (Fig. 7).…”
Section: Ri Of Parameters On Simulation Of Important Climatic Variablessupporting
confidence: 91%
“…For cases where detailed comparison with observation in specific meteorological events is not needed, we recommend to use CLIM for nudging. However, nudging toward CLIM can still affect the physical quantities that are sensitive to the nudged fields (e.g., dust emission in this study and circulation feedback to heating in Lin et al ()).…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, nudging can reduce the divergence of sensitivity experiments caused by natural variability and hence allow for the detection of signal from a substantially smaller amount of data. Examples of studies in this category include Lohmann and Ferrachat (), Kooperman et al (), and Lin et al ().…”
Section: Introductionmentioning
confidence: 99%
“…The large‐scale atmospheric circulation is prescribed using atmospheric nudging. Previous studies on nudging found a reliable adjustment of the atmospheric circulation with the underlying climatology of the other variables in the model not being fundamentally affected (Lin et al, ; Wehrli et al, ; Zhang et al, ). Thus, climatological biases remain after introducing nudging, which was also found for CESM (Wehrli et al, ).…”
Section: Discussionmentioning
confidence: 94%